Functional excitation-inhibition ratio for social anxiety analysis and severity assessment - Chu, Linh Ha; Chau, Chi Que; Kamel, Nidal; Thanh, Huong Ha Thi; Yahya, Norashikin (Frontiers in Psychiatry, 2024)
Social anxiety disorder (SAD) is a prevalent psychiatric condition characterized by an intense fear of and avoidance of social situations. Traditional assessment methods for SAD primarily rely on subjective self-report questionnaires and clinical interviews, which can be prone to biases and inaccuracies. This study investigates the potential of the functional excitation-inhibition (fEI) ratio, derived from EEG data, as an objective biomarker for assessing SAD severity. Resting-state EEG data were collected from 20 control subjects and 60 individuals with mild, moderate, and severe SAD. The fEI ratio was estimated across different EEG bands and compared between control subjects and the SAD groups. Results showed significantly higher fEI ratios in the alpha and low beta bands in individuals with SAD compared to controls, particularly in the prefrontal cortex. Furthermore, there was a positive correlation between the fEI ratio and the severity of social anxiety symptoms within the SAD groups. These findings suggest that the fEI ratio in the alpha and lower beta bands is a promising biomarker for assessing SAD severity and provides insights into the neural mechanisms underlying social anxiety.